Meta-analysis of single-session behavioral interventions to prevent sexually transmitted infections: implications for bundling prevention packages. - Eaton, Lisa A; Huedo-Medina, Tania B; Kalichman, Seth C; Pellowski, Jennifer A; Sagherian, Michael J; Warren, Michelle; Popat, Ami R; Johnson, Blair T (American journal of public health, 2012)
Evidence-based, single-session behavioral interventions are urgently needed for preventing the spread of HIV and other sexually transmitted infections (STIs). To estimate the efficacy of single-session, behavioral interventions for STI prevention, we collected data from 29 single-session interventions (20 studies; n = 52 465) with an STI outcome. Infection with an STI was 35% less likely (odds ratio = 0.65; 95% confidence interval = 0.55-0.77) among intervention group participants than among control group participants. Single-session interventions offer considerable benefits in terms of disease prevention and create minimal burden for both the patient and the provider. Brief and effective STI prevention interventions are a valuable tool and can be readily adapted to bolster the benefits of biomedical technologies focusing on the prevention of HIV and other STIs.
Keywords: Adolescent; Adult; Condoms; Counseling; HIV Infections; Humans; Patient Education as Topic; Sexually Transmitted Diseases; Young Adult